Proof-of-concept Raman spectroscopy study aimed to differentiate thyroid follicular patterned lesions. Issue 1 (December 2017) - Rau, Julietta; Fosca, Marco; Graziani, Valerio; Taffon, Chiara; Rocchia, Massimiliano; Caricato, Marco; Pozzilli, Paolo; Onetti Muda, Andrea; Crescenzi, Anna
Abstract Inter-observer variability and cancer over-diagnosis are emerging clinical problems, especially for follicular patterned thyroid lesions. This challenge strongly calls for a new clinical tool to reliably identify neoplastic lesions and to improve the efficiency of differentiation between benign and malignant neoplasms, especially considering the increased diagnosis of small carcinomas and the growing number of thyroid nodules. In this study, we employed a Raman spectroscopy (RS) microscope to investigate frozen thyroid tissues from fourteen patients with thyroid nodules. To generate tissue classification models, a supervised statistical analysis of the Raman spectra was performed. The results obtained demonstrate an accuracy of 78% for RS based diagnosis to discriminate between normal parenchyma and follicular patterned thyroid nodules, and 89% accuracy – for very challenging follicular lesions (carcinomaversus adenoma). RS translation into intraoperative diagnosis of frozen sections and in preoperative analysis of biopsies can be very helpful to reduce unnecessary surgery in patients with indeterminate cytological reports.